Fluorescent liquid crystals with rod-shaped π-conjugated hydrocarbon core. Issue 2 (26th January 2019) - Buchs, Jens; Geßner, André; Heyne, Benjamin; Janietz, Dietmar; Sawade, Hans
ABSTRACT: Calamitic fluorophores are presented possessing either two phenylethylene or phenylacetylene fragments which are connected via an aromatic entity. The new compounds exhibit smectic C and/or nematic liquid crystalline phases. The chromophores show fluorescence in the blue spectral region. Grafting acrylate functional groups to the termini of naphthalene centred members of the rod-shaped dyes provides new luminescent reactive mesogens. Uniaxial orientation of mixed systems of the acrylate fluorophores with non-emissive reactive benzoate nematogens was achieved by surface-assisted alignment on polyimide orientation layers. The photocrosslinked oriented films display linear polarised photoluminescence upon isotropic excitation. GRAPHICAL ABSTRACT: